The Vagabond Mind: Depression and the Medieval Anchorite - Lazikani, Ayoush Sarmada (The journal of medieval monastic studies, 2017)
There has been, as yet, no sustained scholarship on anchoritic depression' in the high Middle Ages. Situated in burgeoning research on the interplay between literature and medicine, the present article seeks to address this gap. It examines the attempts of authors and readers to define, express, and ultimately soothe depressive and despairing states through the act of reading. Focus will rest on three anchoritic guidance texts from the eleventh to the thirteenth centuries: Goscelin of Saint-Bertin's (c. 1035-1107) Latin Liber confortatorius; Aelred of Rievaulx's (1110-67) Latin De institutione inclusarum; and the English Ancrene Wisse (1215-30). For anchorites, the practice of reading these texts heals and rejuvenates a wearied soul - or, as put by Goscelin, the vagabond mind (mens uagabunda')